Influenza‐specific IgG1+ memory B‐cell numbers increase upon booster vaccination in healthy adults but not in patients with predominantly antibody deficiency. Issue 10 (16th October 2020) - Hartley, Gemma E; Edwards, Emily S J; Bosco, Julian J; Ojaimi, Samar; Stirling, Robert G; Cameron, Paul U; Flanagan, Katie; Plebanski, Magdalena; Hogarth, Philip Mark; O'Hehir, Robyn E; van Zelm, Menno C
Abstract: Background: Annual influenza vaccination is recommended to all individuals over 6 months of age, including predominantly antibody deficiency (PAD) patients. Vaccination responses are typically evaluated by serology, and because PAD patients are by definition impaired in generating IgG and receive immunoglobulin replacement therapy (IgRT), it remains unclear whether they can mount an antigen‐specific response. Objective: To quantify and characterise the antigen‐specific memory B (Bmem) cell compartment in healthy controls and PAD patients following an influenza booster vaccination. Methods: Recombinant hemagglutinin (HA) from the A/Michigan/2015 H1N1 (AM15) strain with an AviTag was generated in a mammalian cell line, and following targeted biotinylation, was tetramerised with BUV395 or BUV737 streptavidin conjugates. Multicolour flow cytometry was applied on blood samples before and 28 days after booster influenza vaccination in 16 healthy controls and five PAD patients with circulating Bmem cells. Results: Recombinant HA tetramers were specifically recognised by 0.5–1% of B cells in previously vaccinated healthy adults. HA‐specific Bmem cell numbers were significantly increased following booster vaccination and predominantly expressed IgG1. Similarly, PAD patients carried HA‐specific Bmem cells, predominantly expressing IgG1. However, these numbers were lower than in controls and did not increase following booster vaccination. Conclusion: We have successfully identified AM15‐specific Bmem cells in healthy controls and PAD patients. The presence of antigen‐specific Bmem cells could offer an additional diagnostic tool to aid in the clinical diagnosis of PAD. Furthermore, alterations in the number or immunophenotype of HA‐specific Bmem cells post‐booster vaccination could assist in the evaluation of immune responses in individuals receiving IgRT. Abstract : We here developed an extensive flowcytometry panel to examine influenza‐specific memory B cells using fluorescently labeled recombinant haemagglutinin (HA) tetramers. Influenza‐specific memory B cells were predominantly IgG1 +, and these were increased following booster vaccination in healthy controls, but not in patients with predominantly antibody deficiency.